رتج ميكل عند الأطفال خبرة مشفى الأسد الجامعي باللاذقية بين عامي 1992-2002 - دوميط, عماد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة على حالات رتج ميكل المكتشفة في مشفى الأسد الجامعي باللاذقية بين عامي: 1992-2002. شملت الدراسة /28/ حالة، قُسمت إلى مجموعتين: ضمت المجموعة الأولى /10/ حالات، وهي حالات رتج ميكل المختلطة. وضمت المجموعة الثانية /18/ حالة، وهي حالات رتج ميكل المكتشفة صدفة أثناء فتح البطن لأسباب أخرى. استؤصل رتج ميكل في /26/ حالة، تبين في /18/ منها وجود مخاطية هاجرة ضمنه. لوحظت أغلب مضاعفات رتج ميكل (النزف، الالتهاب، انسداد الأمعاء) عند الأطفال تحت سن السنتين. تعزى مضاعفات رتج ميكل غالباً إما لوجود مخاطية هاجرة ضمنه، أو لتثبته على جدار البطن. ينصح معظم جراحي الأطفال باستئصال رتج ميكل فور تشخيصه، نظراً لارتفاع معدل إصابته بالمضاعفات عند الأطفال. The study has been made on the cases of Meckel’s diverticulum found in Al-Assad University Hospital in Lattakia between 1992-2002. The study composed of /28/ cases, divided into two groups: The first group consisted of /10/ cases, in which Meckel’s diverticulum was complicated. The second group consisted of /18/ cases, in which Meckel’s diverticulum was found incidentally, during laparotomy made for other reasons. Diverticulectomy was performed in /26/ cases. Ectopic mucosa was found within the diverticulum in /18/ cases. Most of the complications associated with Meckel’s diverticulum (bleeding, inflamation and obstruction) have been found in children less than /2/ years old. The complications of Meckel’s diverticulum are most commonly attributed either to the presence of ectopic mucosa within the diverticulum, or fixation of it to the abdominal wall. Most pediatric surgeons recommend diverticutomy at the time the lesion is found, given the much higher incidence of complications in children.